2000
DOI: 10.1016/s0735-1097(99)00625-7
|View full text |Cite
|
Sign up to set email alerts
|

Local adenovirus-mediated transfer of C-type natriuretic peptide suppresses vascular remodeling in porcine coronary arteries in vivo

Abstract: Adenovirus-mediated CNP gene transfer with the IABC system may be a useful gene therapy to prevent restenosis after PTCA in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…AdLacZ was used as a control. 16 In the present study, AdDNRhoK represents an adenoviral vector encoding RB; however, we confirmed that an adenoviral vector encoding RB/PH(TT) also caused the same inhibitory effect on the constrictive vascular remodeling and vasospastic activity in the present porcine model in vivo (data not shown).…”
Section: Construction Of Adenoviral Vectorssupporting
confidence: 68%
See 1 more Smart Citation
“…AdLacZ was used as a control. 16 In the present study, AdDNRhoK represents an adenoviral vector encoding RB; however, we confirmed that an adenoviral vector encoding RB/PH(TT) also caused the same inhibitory effect on the constrictive vascular remodeling and vasospastic activity in the present porcine model in vivo (data not shown).…”
Section: Construction Of Adenoviral Vectorssupporting
confidence: 68%
“…This catheter is useful for the direct delivery of fluid into the vessel wall in vivo with Ͼ90% efficiency and minimal vascular damage 17 and also for in vivo gene transfer into the coronary artery. 16 AdLacZ and AdDNRhoK (final titer, 4ϫ10 9 pfu in 0.4 mL sorbitol-added lactated Ringer's saline) were injected into the coronary segment in a randomized manner, and then the catheter was deflated and withdrawn.…”
Section: Adenovirus-mediated Gene Transfer Into Porcine Coronary Artementioning
confidence: 99%
“…Expression of β-galactosidase delivered by an Infiltrator was mostly localized around outer media and adventitia, which seems to be related with the height (279 µm) of injector ports. And similar observations were reported by other studies (Morishige et al, 2000;Kingston et al, 2001). Our study suggested that no significant dissemination of adenovirus occurred, since transgene, ectodomain of human TGF β type II receptor mRNA, was localized in the injection segment.…”
Section: Discussionsupporting
confidence: 92%
“…Upregulation of GC-B expression is also seen in the rat carotid artery after a balloon injury [159]. Moreover, adenovirus-mediated CNP gene transfer causes growth inhibition and re-differentiation in cultured vascular SMCs [160] and prevents restenotic changes after a balloon injury in rat carotid and porcine coronary arteries [161,162]. It should be noted, however, that CNP levels in the culture media of the adenovirus-transfected vascular SMCs are approximately 4,000-fold greater than normal [160] and that the endogenous CNP/GC-B system cannot halt progression of proliferative vascular lesions even though activated.…”
Section: Gc-cmentioning
confidence: 99%
“…Thus CNP null mice appear short-lived because of the skeletal abnormalities [174]. The CNP/GC-B signaling pathway has been proposed to play a normal role in the regulation of proliferation and migration of vascular SMCs in proliferative vascular lesions [158][159][160][161][162][163]194]. CNP null mice, however, have no apparent cardiovascular abnormalities [174].…”
Section: F Bnp Transgenic Micementioning
confidence: 99%